New drug target in protozoan parasites: the role of thioredoxin reductase - Andrade, Rosa M.; Reed, Sharon L. (Frontiers in Microbiology, 2015)
Amebiasis causes approximately 70,000 deaths annually and is the third cause of death due to parasites worldwide. It is treated primarily with metronidazole, which has adverse side effects, is mutagenic and carcinogenic, and emergence of resistance is an increasing concern. Unfortunately, better therapeutic alternatives are lacking. Re-purposing of older FDA approved drugs is advantageous to drug discovery since safety and pharmacokinetic effects in humans are already known. In high throughput screening studies, we recently demonstrated that auranofin, a gold containing compound originally approved to treat rheumatoid arthritis, has activity against trophozoites of E. histolytica, the causative agent of amebiasis. Auranofin’s anti-parasitic activity is attributed to its monovalent gold molecule that readily inhibits E.histolytica thioredoxin reductase. This anti-oxidant enzyme is the only thiol-dependent flavo-reductase present in E.histolytica. Auranofin has also shown promising activity against other protozoans of significant public health importance. Altogether, this evidence suggests that auranofin has the potential to become a broad spectrum alternative therapeutic agent for diseases with a large global burden.